Thatched roofs and open sides : the architecture of Chickees and their changing role in Seminole society - Dilley, Carrie (University Press of Florida, 2015)
By examining the past, present, and future of Chickees, Chickee builders, and their role in tribal life, this architectural and cultural history reveals the relationship between the transformation of these structures and the cultural evolution of the Seminole Tribe.